Pengaruh Media Napkin Series Terhadap Peningkatan Pengetahuan dan Sikap Ibu di Sekolah TK Tangerang - Nadya Faradilla; Putri Ronitawati; Nadiyah Nadiyah (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: Food consumption is a major problem in our community, including children. Children are one of the groups that tend to experience nutritional problems, among the causes is low economic level, unbalanced food intake, and low knowledge. To optimize the delivery of balanced nutrition messages to the community, an appropriate and community-based KIA is needed. A way to increase knowledge about nutrition is through the napkin media. Objective: To know the influence of education through nutrition napkin media on the knowledge and attitudes of mothers in early childhood in Tangerang kindergarten. Methods: This study used a Quasy Experimental method with pre-test and post-test in the treatment and control groups, using the research design pre-test post-test control group. 86 samples were used which were divided into two groups, namely, 43 treatment groups and 43 control groups. Results: There is a significant influence on the median score (minimum-maximum) knowledge and attitudes about balanced nutrition before and after the intervention (p <0.05) which means there is an increase in the median value of knowledge and attitude about nutrition balanced. Conclusion: The Napkin Nutrition Series Media is effective in increasing the knowledge and attitude of mothers to recall the information provided.